Visibility layers: A framework for systematising the gender gap in Wikipedia content - Pablo Beytía Reyes; Claudia Wagner (Internet Policy Review, 2022)
The gender gap in Wikipedia content is a complex phenomenon that comprises several asymmetries, discursive dimensions, and social concerns. However, there is no theoretical framework to organise this complexity consistently. Based on writings by Foucault, Deleuze and Tkacz, we interpret Wikipedia as a 'field of visibility' and provide a framework to systemise its content gaps. Then we use that model to organise the complexity of the content gender gap on Wikipedia, performing a systematic overview of the asymmetries tested in empirical research. We suggest that this analysis is relevant for the effective planning of governance processes that seek to avoid female or non-male subordination in digital platforms' discourses.
Keywords: 300; gender; Digital discourse; Platform bias; Digital platforms; Gender bias; Asymmetric Regulation